Proceedings of the third regional groundnut workshop for Southern Africa. Lilongwe (Malawi). 13-18 March 1988 - Bock, K.R.; Cole, D.L.; Hildebrand, G.L.; Nigam, S.N.; Wightman, J.A. (Patancheru (India), 1989)
Sumarios (Es, Fr, Pt)
Ilus.; 33 ref.
Keywords: ENFERMEDADES DE LAS PLANTAS; RESISTENCIA A LA ENFERMEDAD; FUNGICIDAS; DESARROLLO RURAL; ANALISIS ECONOMICO